Criteria, indicators and levels of formation of value and conceptual orientations of high school students in the process of studying mathematical disciplines - Баруліна, Юлія Олександрівна (Pedagogy of Higher and Secondary Education, 2019)
Barulinа Yu. А. Criteria, indicators and levels of formation of value and conceptual orientations of high school students in the process of studying mathematical disciplines. The article deals with the definition of «criterion» and «indicator» in the reference and scientific literature. The views of various scholars on these concepts are discusses. Criteria, indicators and levels of formation of value and conceptual orientations of high school students in the process of studying mathematical disciplines are defined to further research on this topic.